Adsorption of methylene blue by bismuth impregnated biochar of different biomass materials: pore structure and surface chemistry characteristics. Issue 10 (5th July 2022) - Li, Peiyi; Su, Yuting; Hu, Zhanbo; Zheng, Yukai; Zhou, Qian; Ouyang, Xiao
Abstract: In this study, three different types of biochar (biomass materials were beech wood, corncob, and bamboo) were loaded with bismuth to form bismuth impregnated biochars (named respectively as Bi@WBC, Bi@CBC, and Bi@BBC) to investigate their properties (pore structure and surface chemistry characteristics) on methylene blue (MB) removal capacities. Three bismuth impregnated biochars made from different biomass materials were ranked for their adsorption capacity of MB as follows: Bi@WBC > Bi@CBC > Bi@BBC, in which Bi@WBC showed the largest Langmuir adsorption capacity of 178.59 mg g −1 . While the specific surface area (SSA) and pore volume of Bi@WBC were the largest (accounting for 477.74 m 2 g −1 and 0.15 cm 3 g −1, respectively), according to the FTIR and XPS results, Bi@WBC (72.3%) exhibited a higher proportion of BiO bonds than the Bi@CBC (52.3%) and Bi@BBC (48.4%) did. Conclusively, the rich porous structure and surface functional groups of Bi@WBC affected the adsorption capacity of MB, and the chemical adsorption provided the main contribution. © 2022 Society of Chemical Industry (SCI).